Martin O. Heisler (ed.), The Annals of the American Academy of Political and Social Science, vol. 512: »The Nordic Region: Changing Perspectives in International Relations«, Newbury Park, London, New Delhi: Sage Publications, 1990, 2285., 12.95. - Amstrup, Niels (Politica, 1991)
-